Influence of Tool Force on Microstructure and Mechanical Properties in AA2024-O Alloy during Friction Stir Welding - Karmanov, V. V.; Kameneva, A. L. (New Approaches in Engineering Research Vol. 5, 2021)
In this paper, the microstructure of the weld from the AA2024 alloy is highly dependent on the heat input in the weld, and therefore it is necessary to understand thebrelationship between these characteristics to improve the mechanical properties of the weld. The microstructure of the weld from the AA2024 alloy is highly dependent on the heat input in the weld, and therefore it is necessary to understand the relationship between these characteristics to improve the mechanical properties of the weld. The effect of the microstructure in various zones of the weld on its microhardness has been ascertained. The structure of various weld zones was studied depending on the heat input to the weld. Therefore, the experiment was performed at different values of the external axial force and the values of the constant speed of the rotation of the tool and welding. The dependence of the microhardness and microstructure of the weld zones on the temperature gradient in both normal and traverse directions has been established.